O impacto da abertura ao comércio exterior da década de 1990 no setor têxtil brasileiro - Emery, Márcio de Morais (2007)
This work tries to contribute to the debate regarding the foreign trade policy. The objective is to identify the impact on the Brazilian textile sector, result of the foreign trade liberalization of 1990 s, distinguishing specific impacts for determined segments, from the broadly distributed for the entire sector. The research hypothesis is that although the impact was perceived in different ways by the various segments of the sector, there was a common standard: the mechanization of the production in search of competitiveness and the consequent workforce reduction in the process. It reviews the textile sector, considering its dynamics, its origins, its development and its socioeconomic relevance. It argues the foreign trade liberalization process of the 1990 s in its diverse aspects and follows with the review of the impact in the various textile segments. The rearrangement in the textile sector s labor force brings complex impacts to the economic and social fields